2015
DOI: 10.3791/52372
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Foodborne Bacterial Pathogens from Individual Filth Flies

Abstract: There is unanimous consensus that insects are important vectors of foodborne pathogens. However, linking insects as vectors of the pathogen causing a particular foodborne illness outbreak has been challenging. This is because insects are not being aseptically collected as part of an environmental sampling program during foodborne outbreak investigations and because there is not a standardized method to detect foodborne bacteria from individual insects. To take a step towards solving this problem, we adapted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
(4 reference statements)
0
13
1
Order By: Relevance
“…We have previously reported that C. sakazakii colonies could not be recovered from some PCR-positive samples while using this combined approach, likely due to the PCR being positive when other closely related bacterial genera , such as Citrobacter freundii , are present in the samples [ 7 , 27 ]. Additionally, besides C. sakazakii a number of other Enterobacteriaceae are α-glucosidase positive, therefore the co-isolation of those organisms from samples with highly complex microbiota (such as the fly’s alimentary canal) could lower the efficiency of recovery of C. sakazakii from the chromogenic media used [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously reported that C. sakazakii colonies could not be recovered from some PCR-positive samples while using this combined approach, likely due to the PCR being positive when other closely related bacterial genera , such as Citrobacter freundii , are present in the samples [ 7 , 27 ]. Additionally, besides C. sakazakii a number of other Enterobacteriaceae are α-glucosidase positive, therefore the co-isolation of those organisms from samples with highly complex microbiota (such as the fly’s alimentary canal) could lower the efficiency of recovery of C. sakazakii from the chromogenic media used [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Immobilized flies were then transferred to a disposable Petri dish containing 70 % alcohol for 2 min. Using a dissecting scope, three adult female house flies were randomly sub-sampled per each glass jar (n = 48 per each foodborne bacterium) and individually transferred to an autoclaved two ml tube to be surface-disinfected and their alimentary canals dissected as described by Pava-Ripoll , et al [ 27 ]. The alimentary canals of maternal house flies were individually evaluated for the presence of the target bacteria as described in sections below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently 1 ml of the above culture was transferred into 9 ml Fraser (Oxoid Ltd.) for 48 h at 37°C with shaking (220 rpm). Flies and cockroach samples were pulverized before culturing because that L. monocytogenes could exist on the body surface as well as the alimentary canal of a single fly ( Pava-Ripoll et al, 2015 ). Enriched broth was then spread onto brilliance listeria agar (Oxoid Ltd.) for 24–36 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%